2020
DOI: 10.21203/rs.3.rs-25447/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Qualitative study exploring the barriers to menstrual hygiene management faced by adolescents and young people with a disability, and their carers in the Kavrepalanchok district, Nepal

Abstract: Background: Menstrual hygiene management (MHM) is a recognised public health, social and educational issue, which must be achieved to allow the realisation of human rights. People with disabilities are likely to experience layers of discrimination when they are menstruating, but little evidence exists.Methods: The study aims to investigate barriers to MHM that people with disabilities and their carers, face in the Kavrepalanchok, Nepal, using qualitative methods. Twenty people with disabilities, aged 15-24, wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…For instance, people with disabilities were stopped using public toilets in a study in Uganda because it was believed that disability is 'dirty' and 'contagious' [16,17]. Therefore, menstruators with disabilities may experience a compounded sense of shame and discrimination with both disability and menstruation considered taboo in many settings [18][19][20][21][22]. These issues negatively impact menstruators' ability to participate fully in daily life: the latest Joint Monitoring report highlights that women with disabilities were 50% less likely to participate in usual activities when they were menstruating compared to those without disabilities [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, people with disabilities were stopped using public toilets in a study in Uganda because it was believed that disability is 'dirty' and 'contagious' [16,17]. Therefore, menstruators with disabilities may experience a compounded sense of shame and discrimination with both disability and menstruation considered taboo in many settings [18][19][20][21][22]. These issues negatively impact menstruators' ability to participate fully in daily life: the latest Joint Monitoring report highlights that women with disabilities were 50% less likely to participate in usual activities when they were menstruating compared to those without disabilities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Menstruators with disabilities, especially those with intellectual impairments, often receive little or no information about menstruation, or how to manage it hygienically and with dignity [18]. Furthermore, approximately 190 million people with disabilities rely on informal or professional caregivers for assistance, which may include supporting menstrual health [24].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate knowledge of disability, incontinence and menstruation, training and resources provided on these topics; services provided to people with and without disabilities, and caregivers, and provision of incontinence and / or menstrual materials 1 healthcare professional, working in a rural location 1 healthcare professional, working in an urban location To explore WASH service implementation, knowledge of the issues faced by people with and without disabilities, how to address them, and challenges related to doing that 2 professionals working in the WASH sector * PhotoVoice is a visual research methodology, in which participants are loaned a camera, shown how to take photos and asked to take photos that represent their experiences related to the study issues [38] . The methodology has been used to explore WASH issues, including MHM and incontinence, in Nepal [39] , Kenya [40] , Malawi [5] , Pakistan [41] and Ghana [42] .…”
Section: Professional Working In the Area Of Washmentioning
confidence: 99%
“…
The pandemic has been exacerbating existing inequalities between women and men in almost all areas of life [3]. However, menstrual discrimination (taboos, stigma, abuses, restrictions, discriminations) has not been studied in the context of the pandemic at least in Asia in spite of the well published earlier concerns in regard to the politics of menstruation during the pandemic by Jahan [11], by the first data published by Aolymat on women in Jordan [12] and several other authors [13][14][15].Therefore, this study was conducted to fill this gap mainly by contributing to a better understanding of menstrual dignity and the experiences of women and LGBTQI during menstruation and observed changes during the COVID-19 pandemic.
MethodologyThe study adopted a mixed-method qualitative method integrating qualitative components based on open questions with a short structured questionnaire to elicit general social data and basic information on menstruation related health literacy developed for the study. We also decided to use a multi/transcultural approach by recruiting participants from different countries and cultures as culture has been identified as a major factor in menstrual practices and related
…”
mentioning
confidence: 99%
“…The pandemic has been exacerbating existing inequalities between women and men in almost all areas of life [3]. However, menstrual discrimination (taboos, stigma, abuses, restrictions, discriminations) has not been studied in the context of the pandemic at least in Asia in spite of the well published earlier concerns in regard to the politics of menstruation during the pandemic by Jahan [11], by the first data published by Aolymat on women in Jordan [12] and several other authors [13][14][15].…”
mentioning
confidence: 99%